Ga and Ti co-doped In2O3 films for flexible amorphous transparent conducting oxides. Issue 10 (15th May 2022) - Kang, Chaeyoung; Seok, Hae-Jun; Kim, Seong-Won; Beigtan, Mohadese; Kim, Yunseok; Kim, Han-Ki
Abstract: We designed Ga and Ti co-doped In2 O3 (IGTO) films to use as a flexible and transparent amorphous conducting oxide electrode in thin film heaters (TFHs) and flexible touch screen panels (FTSPs) for automobiles. The properties of the IGTO electrodes deposited on cyclic olefin copolymer (COP) at room temperature were investigated as a function of the O2 /(Ar + O2 ) flow ratio, to confirm the best sputtering condition for transparent and flexible electrode. Depending on the oxygen flow ratio, the IGTO/COP electrodes showed sheet resistance of (39.3 – 1.57) × 10 4 Ohm/sq, an average transmittance of (84.90 – 87.12) % at visible wavelength area, and a surface roughness of (0.95 – 3.23) nm. In addition, IGTO/COP samples exhibited good mechanical flexibility with critical bending radius of 3 mm, which is enough to be used as FTSPs. From the previously mentioned results, we found the amorphous IGTO/COP to be a promising flexible and transparent electrode for curved TFHs and FTSPs. The flexible IGTO/COP TFHs demonstrated a saturated temperature of 78.6 °C when applied with low operating direct current (DC) of 8 V, due to its low sheet resistance. In addition, the IGTO/COP FTSPs showed very stable touch sensitivity, even at a bent state. We found that the optimized IGTO/COP is a promising flexible and transparent electrode for next-generation automobiles.